The Value of Further Education in Security Sector Reform: Autoethnographic Reflections from Palestine, Lebanon, and Georgia. Issue 4 (8th August 2022) - Jacobs, An; Rossi, Norma
ABSTRACT: Although Security Sector Reform (SSR) is widely regarded as a vital element of peacebuilding, its implementation has remained largely disappointing. In recent years, the academic literature has witnessed an intensifying debate on the need to close the policy-implementation gap in SSR. This article contributes to the debate on the need for a second generation SSR by exploring the value of further education (FE) programmes through an autoethnographic approach of FE courses delivered in Palestine, Lebanon, and Georgia. We argue that FE can enhance a holistic approach to SSR, contributing to horizontal and vertical integration and fostering a long-term strategic vision.